Evolution in the concept of sunnah during the first four generations of muslims in relation to the development of the concept of an authentic Hadīth as based on recent western scholarship - Duderija, A. (Brill Academic Publishers, 2012)
The aim of this article is to trace the evolution in the meaning of the concept of Sunnah prior to its classical definition, which largely confluences it with the concept of an authentic( ṣaḥīḥ) Ḥadīth as defined by the classical Ḥadīth sciences. This article will first describe the semanico-contextual changes in the meaning of the term Sunnah during the period under examination and then present a chronological analysis of the development of the concept ‘Sunnah’ in relation to the development of the concept ‘authentic Ḥadīth’. This article argues that during the first four generations of Muslims, the concept ‘Sunnah’ remained epistemologically independent of the concept ‘authentic Ḥadīth’ and that evaluation of Sunnah compliance with a certain practice or belief remained methodologically independent to that of the concept of an authentic Ḥadīth, as defined by classical ʿulūm al-ḥadīth sciences.